Tundra landscape heterogeneity, not interannual variability, controls the decadal regional carbon balance in the Western Russian Arctic. (9th September 2018) - Treat, Claire C.; Marushchak, Maija E.; Voigt, Carolina; Zhang, Yu; Tan, Zeli; Zhuang, Qianlai; Virtanen, Tarmo A.; Räsänen, Aleksi; Biasi, Christina; Hugelius, Gustaf; Kaverin, Dmitry; Miller, Paul A.; et al.
Abstract: Across the Arctic, the net ecosystem carbon (C) balance of tundra ecosystems is highly uncertain due to substantial temporal variability of C fluxes and to landscape heterogeneity. We modeled both carbon dioxide (CO2 ) and methane (CH4 ) fluxes for the dominant land cover types in a 100‐km 2 sub‐Arctic tundra region in northeast European Russia for the period of 2006–2015 using process‐based biogeochemical models. Modeled net annual CO2 fluxes ranged from −300 g C m −2 year −1 [net uptake] in a willow fen to 3 g C m −2 year −1 [net source] in dry lichen tundra. Modeled annual CH4 emissions ranged from −0.2 to 22.3 g C m −2 year −1 at a peat plateau site and a willow fen site, respectively. Interannual variability over the decade was relatively small (20%–25%) in comparison with variability among the land cover types (150%). Using high‐resolution land cover classification, the region was a net sink of atmospheric CO2 across most land cover types but a net source of CH4 to the atmosphere due to high emissions from permafrost‐free fens. Using a lower resolution for land cover classification resulted in a 20%–65% underestimation of regional CH4 flux relative to high‐resolution classification and smaller (10%) overestimation of regional CO2 uptake due to the underestimation of wetland area by 60%. The relative fraction of uplands versus wetlands was key to determining the net regional C balance at this and other Arctic tundra sites because wetlands were hot spots for C cycling in Arctic tundra ecosystems. Abstract : We modeled the regional carbon balance of sub‐Arctic tundra over a decade in a region with lakes, wetlands, and uplands using process‐based biogeochemical models. Interannual variability over the decade was relatively small in comparison with variability among the land cover types. Wetlands were hot spots for C cycling in this sub‐Arctic tundra ecosystem. Capturing the relative fraction of uplands versus wetlands was key to determining the net regional C balance at this and other Arctic tundra sites.